The Households Characteristics of Sufficient Water in Kyrgyzstan: An Analysis of The Multiple Indicator Cluster Survey (MICS) - Suryani, Dyah; Suyitno, Suyitno; Yunus, Mohd (Journal of Health and Nutrition Research, 2025)
This study investigates the relationship between household characteristics and access to sufficient water in Kyrgyzstan, utilizing secondary data from the 2023 Multiple Indicator Cluster Survey (MICS). Employing a quantitative approach with a cross-sectional design, the analysis encompassed univariate, bivariate (Chi-square test), and multivariate (binary logistic regression) methods. The sample comprised 6,615 households, with findings indicating that most households are of productive age, possess secondnoary to higher education, reside in rural areas, and have access to sufficient water. Economic and regional distributions within the sample are relatively balanced, reflecting the broader population's diversity. Multivariate analysis revealed that access to sufficient water is significantly influenced by regional location, household welfare level, and ethnicity; regions such as Issyk-Kul, Bishkek, and Jalal-Abad exhibit higher access, while Talas and Chui show lower access. Demographic factors like gender, age, and place of residence did not significantly affect water access. These findings underscore the necessity for targeted policies that address disparities in water access, focusing on disadvantaged regions and low-income households to promote equitable access to sufficient water